Interventions, outcomes and outcome measurement instruments in stillbirth care research: A systematic review to inform the development of a core outcome set. (29th March 2023) - Bakhbakhi, Danya; Siassakos, Dimitrios; Davies, Anna; Merriel, Abi; Barnard, Katie; Stead, Emma; Shakespeare, Clare; Duffy, James M. N.; Hinton, Lisa; McDowell, Karolina; Lyons, Anna; Fraser, Abigail; et al.
Abstract: Background: A core outcome set could address inconsistent outcome reporting and improve evidence for stillbirth care research, which have been identified as an important research priority. Objectives: To identify outcomes and outcome measurement instruments reported by studies evaluating interventions after the diagnosis of a stillbirth. Search strategy: Amed, BNI, CINAHL, ClinicalTrials.gov, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, Embase, MEDLINE, PsycINFO, and WHO ICTRP from 1998 to August 2021. Selection criteria: Randomised and non‐randomised comparative or non‐comparative studies reporting a stillbirth care intervention. Data collection and analysis: Interventions, outcomes reported, definitions and outcome measurement tools were extracted. Main results: Forty randomised and 200 non‐randomised studies were included. Fifty‐eight different interventions were reported, labour and birth care (52 studies), hospital bereavement care (28 studies), clinical investigations (116 studies), care in a multiple pregnancy (2 studies), psychosocial support (28 studies) and care in a subsequent pregnancy (14 studies). A total of 391 unique outcomes were reported and organised into 14 outcome domains: labour and birth; postpartum; delivery of care; investigations; multiple pregnancy; mental health; emotional functioning; grief and bereavement; social functioning; relationship; whole person; subsequent pregnancy; subsequent children and siblings and economic. A total of 242 outcome measurement instruments were used, with 0–22 tools per outcome. Conclusions: Heterogeneity in outcome reporting, outcome definition and measurement tools in care after stillbirth exists. Considerable research gaps on specific intervention types in stillbirth care were identified. A core outcome set is needed to standardise outcome collection and reporting for stillbirth care research.